The Prognostic Value of Serum CRP in Acute Leukemia - Alhasan, Hala; Feras Hussein; Rama Ibrahim (Latakia University Journal -Medical Sciences Series, 2024)
Objective: Acute Leukemia is one of the malignant hematological disorders with an increasing incidence rate worldwide. As tumor cells stimulate liver to produce inflammatory cytokines, serum CRP levels are elevated. The prognostic significance of serum CRP as sensitive, easily analyzable, and cost-effective tumor marker in acute leukemia has been questioned. Methods: The study included 54 newly diagnosed patients with acute leukemia (30 with acute lymphoblastic leukemia and 24 with acute myeloid leukemia). CRP levels were measured by Immunoturbidemetry with using a Mindray analyser. Patients were divided into two groups based on their to serum CRP levels: Group (1) CRP ≤ 7.5 mg/L, Group (2) CRP > 7.5 mg/L. Results: Overall Survival (OS) rate was statistically higher in the Group CRP ≤ 7.5 mg/L. 84.8 % Conclusions: Pre-treatment serum CRP levels is an important prognostic marker in acute leukemia patients, with high CRP levels indicating poor prognosis and lower survival rates. CRP can be used as a routine, cost-effective, and easily analyzable test.